A Novel Approach to Design SRAM Cells for Low Leakage and Improved Stability - Tripti Tripathi; Durg Singh Chauhan; Sanjay Kumar Singh (Journal of Low Power Electronics and Applications, 2018)
The semiconductor electronic industry is advancing at a very fast pace. The size of portable and handheld devices are shrinking day by day and the demand for longer battery backup is also increasing. With these requirements, the leakage power in stand-by mode becomes a critical concern for researchers. In most of these devices, memory is an integral part and its size also scales down as the device size is reduced. So, low power and high speed memory design is a prime concern. Another crucial factor is the stability of static random-access memory (SRAM) cells. This paper combines multi threshold and fingering techniques to propose a modified 6T SRAM cell which has high speed, improved stability and low leakage current in stand-by mode of the memory cell. The simulations are done using the Cadence Virtuoso tool on UMC 55 nm technology.